PENGEMBANGAN KEUNGGULAN BERSAING TENAGA PENDIDIK PADA SEKOLAH ISLAM - isropil Siregar; Mukhtar; Kasful Anwar; Mahmud MY (LPPM Universitas Cipta Mandiri, 2024)
This article discusses in depth the competitive advantage of Islamic educational institutions today. Competitive advantage is a position that must be achieved if you want to survive in the fierce competition among educational actors. Providing quality services, quality services, a variety of results that pamper customer choices, the availability of graduates and price advantages are conditions that make schools superior to competitors in competition. Competitive advantage has the function of helping people have a very high capacity so that they understand the opportunities that come with continuing to improve school excellence, which can be utilized for the welfare of the development of the nation and state. Competitive advantage as a mediating influence of quality innovation and educational orientation on parental, school and foundation satisfaction. To build the best educational services, especially in the current era, schools are faced with the dynamics of the external environment. The external environment of this school is a strategic environment where competencies are persistent and cannot be stopped or terminated. Therefore, a new conception of school excellence is needed that can achieve service excellence to maintain the value of helping students from their participation in education. So, schools must be present in balance with good quality so that they have a competitive advantage. Openness to interact with various strategic supports is a very important trait and a tool to move faster, and also a tool to develop competitive advantage.